2004
DOI: 10.1097/00042752-200409000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Neovascularization and Pain in Abnormal Patellar Tendons of Active Jumping Athletes

Abstract: This study indicates that the presence of neovascularization in abnormal patellar tendons is associated with greater tendon pain compared with abnormal tendons without neovascularization in active jumping athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
85
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 9 publications
9
85
2
1
Order By: Relevance
“…7,31 This increase is typical in those who have had plantar fasciitis for less than 12 months, and has been associated with greater intensity of pain. 31 Similar vascularization has been observed in patients with Achilles, 23,36 patellar, 9 and rotator cuff tendinopathy. 18 The intensity of pain with chronic tendinopathy has also been found to be greater in patients with tendon vascularization compared to those without.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…7,31 This increase is typical in those who have had plantar fasciitis for less than 12 months, and has been associated with greater intensity of pain. 31 Similar vascularization has been observed in patients with Achilles, 23,36 patellar, 9 and rotator cuff tendinopathy. 18 The intensity of pain with chronic tendinopathy has also been found to be greater in patients with tendon vascularization compared to those without.…”
supporting
confidence: 56%
“…18 The intensity of pain with chronic tendinopathy has also been found to be greater in patients with tendon vascularization compared to those without. 9,10,38 Alfredson 2 proposed that vascularization in diseased tendons is one of the potential mediators of pain in tendinopathy, nerve ingrowth associated with new vessels being the cause of pain reported by patients.…”
mentioning
confidence: 99%
“…This finding suggests that angiogenesis plays an important role in pain-experienced in tendinopathy condition [6,7]. These data are in accordance with clinical studies showing that strategies to destroy neovessels (i.e local injection of a sclerosing agent, polidocanol) lead to pain improvement [7]. Etamsylate, an inhibitor of fibroblast growth factor (FGF), when locally applied, supresses FGF-driven angiogenesis [8,9].…”
Section: Discussionsupporting
confidence: 66%
“…It has been reported that nerves appear to travel in close association to tendon neovessels [5]. This finding suggests that angiogenesis plays an important role in pain-experienced in tendinopathy condition [6,7]. These data are in accordance with clinical studies showing that strategies to destroy neovessels (i.e local injection of a sclerosing agent, polidocanol) lead to pain improvement [7].…”
Section: Discussionsupporting
confidence: 62%
“…Neovascularization has gained increasing attention in rheumatology and in human tendon studies (50)(51)(52)(53). Color and power Doppler analyses can demonstrate hyperemia in painful tendons (54), and therapy with sclerosing agents shows promise (55).…”
Section: Discussionmentioning
confidence: 99%